Grammar Analysis in Tourism Text: A Linguistic Study of “What’s the Problem with Overtourism?” - Wardhana, I Gede Neil Prajamukti; Ni Luh Desy Suari Dewi (LITERA : Jurnal Bahasa Dan Sastra, 2026)
This study aims to analyze grammatical structures used in the tourism article “What’s the Problem with Overtourism?” written by Leahy (2023) and published in National Geographic Traveler. The research focuses on identifying and describing various grammatical features, including tenses, passive voice, gerund and infinitive constructions, and relative clauses, to reveal how grammatical choices shape meaning and readability in tourism discourse. Using a qualitative descriptive approach, this study finds that the author employs a range of grammatical patterns to convey factual information, emphasize ongoing global concerns, and maintain a balance between persuasive and informative tones. The use of present simple and perfect tenses dominates the text, reflecting both timeless truths and current relevance of overtourism issues. Passive constructions are strategically used to emphasize processes over agents, while gerund and infinitive forms add fluidity and continuity to the narrative. The findings contribute to a deeper understanding of grammar use in professional tourism writing and provide pedagogical insights for English learners, especially those in tourism and communication studies.